2021
DOI: 10.1521/soco.2021.39.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Does Temporal Distance Influence Abstraction? A Large Pre-Registered Experiment

Abstract: Construal level theory has been extraordinarily generative both within and beyond social psychology, yet the individual effects that form the empirical foundation of the theory have yet to be carefully probed and precisely estimated using large samples and preregistered analysis plans. In a highly powered and preregistered study, we tested the effect of temporal distance on abstraction, using one of the most common operationalizations of temporal distance (thinking about a future point in time that is one day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
0
15
1
Order By: Relevance
“…However, more recent higher-powered replications did not observe a predicted effect of likelihood on abstraction (Calderon et al, 2020), or of temporal distance on abstraction (Bar-Anan, 2009). These findings are in conflict with a recent high-powered and preregistered study that did confirm a moderate effect of d = 0.276 (Sánchez et al, 2021).…”
Section: Motivation For the Current Researchcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, more recent higher-powered replications did not observe a predicted effect of likelihood on abstraction (Calderon et al, 2020), or of temporal distance on abstraction (Bar-Anan, 2009). These findings are in conflict with a recent high-powered and preregistered study that did confirm a moderate effect of d = 0.276 (Sánchez et al, 2021).…”
Section: Motivation For the Current Researchcontrasting
confidence: 99%
“…Greater psychological distance leads to a higher construal level or more abstract representation of phenomena (Liberman & Trope, 1998Trope & Liberman, 2003, 2011. For example, participants indicated a greater preference to describe the activity, 'filling out a personality test' as 'revealing what you're like' (rather than 'answering questions') when thinking about their life further in the future (Sánchez et al, 2021). This straightforward theoretical framework has inspired a variety of applications of psychological science to real-world problems, including important issues such as the way people think about infectious diseases (e.g., Cai & Leung, 2020;Li et al, 2020;Van Lent et al, 2017) and climate change (e.g., Brügger, 2020;Brügger et al, 2016;Chu & Yang, 2019;Jones et al, 2017;Keller et al, 2021;Loy & Spence, 2020;Maiella et al, 2020;Reczek et al, 2018;Rickard et al, 2016;Schuldt et al, 2018;Spence et al, 2012;Wang et al, 2019), with some even stating that "the key problem [underlying climate change] is psychological distance" (Van Lange & Huckelba, 2021, p.49).…”
Section: Publication Bias In Research On Construal Level Theorymentioning
confidence: 99%
“…We recruited participants from the crowd-sourced website Prolific. Using websites of this kind is common in the literature (e.g., Krüger et al 2014;Sánchez et al, 2021). The exact procedures and materials, as well as supplementary analyses and all the data are available on the Open Science Framework (https://osf.io/kgrs9/).…”
Section: General Methodsmentioning
confidence: 99%
“…The concrete option describes how the action would be performed (e.g., "writing things down"). It is argued that those who think about the actions in more abstract terms will more often choose the abstract options, compared to those who think about the actions in concrete terms (e.g., Fujita et al, 2006;Liberman & Trope, 1998;Sánchez et al, 2021). in an abstract way, we mean thinking about its purpose and overall significance.…”
Section: Study 1: Why and How -The Behavior Identification Formmentioning
confidence: 99%
“…While Gouseti (2016) demonstrated that there is a relationship between psychological distance and worry about crime, further research is needed to test whether the processes involved in CLT are valid in the context of an individual’s natural environment. Methodologically, the theoretical constructs associated with CLT have been predominantly tested under experimental conditions (Bar-Anan et al, 2006; Gouseti, 2016; Liberman & Trope, 1998; Sánchez et al, 2021; Soderberg et al, 2015; Trope & Liberman, 2010; Wakslak & Trope, 2009). Regarding CLT’s application to fear of crime, Gouseti (2016) notes that an experimental design may not have captured the way in which psychological distance shapes fear of crime in a natural environment.…”
Section: Review Of Literaturementioning
confidence: 99%